Original paperClinical Study and Management of Secondary Peritonitis due to Perforated Hollow Viscous - Ramachandra, Mathikere Lingaiah; Jagadesh, Bellary; Chandra, Sathees B.C. (Archives of Medical Science, 2007)
Introduction: Secondary peritonitis is an inflammation of the peritoneum caused by another condition, most commonly the spread of an infection from the digestive organs or bowels. This paper aims to present a clinical study and management of secondary peritonitis due to hollow viscous. In this study, peritonitis cases were analyzed with respect to their aetiology; clinical features, treatment, complications and management strategies were discussed. Material and methods: Fifty cases of secondary peritonitis were studied, who were admitted and treated in various surgical units between January 2003 and November 2004. The cause of secondary peritonitis was diagnosed, initially, based on the symptoms and clinical findings on presentation. Then all cases were subjected to detailed clinical examination and laboratory and radiological investigations for thorough analysis. Results: It was observed that perforation of peptic ulcer was the most commonly encountered perforation (64%), followed by small bowel perforations (24%) and then appendicular perforations (12%). The highest incidence of secondary peritonitis (32%) was observed in the age group of 21 to 30 years. Males were predominantly affected with a male to female ratio of 9:1. We recorded 14% mortality in this series. Conclusions: Secondary peritonitis is still a severe disease with high mortality and mandates timely surgical intervention. Perforation of peptic ulcer was the most commonly encountered cause of secondary peritonitis (64%). A variety of operative procedures adopted in this series of patients were fairly successful. Wound infection was the most common complication, occurring in 38% of cases, followed by subphrenic abscess and pelvic abscess (10%).